Socioeconomic, demographic and lifestyle factors associated with dietary patterns of women living in Southern Brazil Fatores sócio-econômicos, demográficos e de estilo de vida associados com padrões alimentares de mulheres residentes no Sul do Brasil - Adriana Lenz; Maria Teresa Anselmo Olinto; Juvenal S. Dias-; Ana Luisa Alves; Marcos Balbinotti; Marcos Pascoal Pattussi; Diego Garcia Bassani (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
This study focused on the association between dietary patterns and socio-demographic and lifestyle factors. A population-based cross-sectional study was performed in 1,026 adult women from Southern Brazil. Dietary patterns were identified using principal components analysis. In the multivariable analysis, a Poisson regression model was used to estimate the prevalence ratio and 95%CI. Wealthier women were more likely to follow healthy diets. A Low Cost Healthy Diet was more prevalent among women with a partner, and a High Cost Healthy Diet was more prevalent among women not currently working and who exercised regularly. Women with lower education levels were less likely to follow a Low Cost Healthy Diet, but more likely to follow the Higher-Risk Low Cost Diet. The Low Cost Higher-Risk Diet was more prevalent among women with a lower income. Low and medium cost healthy diets were positively associated with age. The results showed that women's dietary choices are influenced by socioeconomic factors and are not only dependent on food prices. Para identificar fatores relacionados com padrões alimentares, realizou-se um estudo transversal de base populacional com uma amostra de 1.026 mulheres entre 20 a 60 anos, no Sul do Brasil. Os padrões alimentares foram identificados com análise de componentes principais. Razões de prevalência e intervalos de 95% de confiança foram calculados com regressão de Poisson. Após ajustamento, os padrões alimentares saudáveis foram mais prevalentes em mulheres com melhor escolaridade e classe econômica. Padrão Saudável de Baixo Custo foi mais prevalente entre mulheres casadas/união e Padrão Saudável de Alto Custo naquelas que não trabalhavam e tinham atividade física regular. Mulheres com baixa escolaridade foram menos prováveis de seguir o Padrão Saudável de Baixo Custo, e sim mais prováveis de seguir Padrão de Risco de Baixo Custo. O Padrão de Risco de Baixo Custo também foi mais prevalente entre as mulheres de baixa renda. Padrões alimentares saudáveis de médio e baixo custo foram positivamente associados com a idade. Nossos resultados evidenciam a desigualdade sócio-econômica na escolha feminina do padrão alimentar, mas não apenas definida pelo preço dos alimentos.